Peer conformity and online gaming intensity: Analysis of emotional regulation mediation in adolescents - Hardiyantina Sambo; Suryani Harjo; Amanah Surbakti; Nellinda Syafitri (Universitas Ahmad Dahlan, 2026)
Adolescence is characterised by heightened sensitivity to peer influence and increased engagement in online gaming. Although the relationship between peer conformity and gaming intensity has been widely established, limited research has examined the mediating roles of distinct emotion regulation strategies, particularly in non-metropolitan socio-cultural contexts such as Kutacane, Indonesia. This study employed a quantitative cross-sectional survey design involving 320 secondary school students recruited through convenience sampling. Data were collected using standardised self-report questionnaires and analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicated that peer conformity was strongly and positively associated with online gaming intensity. It was also positively associated with expressive suppression and more weakly associated with cognitive reappraisal. Of the two emotion regulation strategies, only expressive suppression significantly mediated the relationship between peer conformity and gaming intensity, whereas cognitive reappraisal did not demonstrate a significant mediating effect. These findings suggested that peer conformity served as the primary driver of intensive gaming behaviour, while expressive suppression operated as a secondary psychological mechanism. This study contributes theoretically by differentiating the roles of emotion regulation strategies within a single mediation model and integrating Social Identity Theory and Coping Theory. Practically, the findings highlight the importance of interventions that address peer group norms, strengthen adaptive emotion regulation skills, and provide alternative social activities beyond gaming.